2017
DOI: 10.1021/acs.molpharmaceut.6b00995
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Preparation of Site-Specific Antibody–Drug Conjugates Using Cysteine Insertion

Abstract: Antibody-drug conjugates (ADCs) are a class of biopharmaceuticals that combine the specificity of antibodies with the high-potency of cytotoxic drugs. Engineering cysteine residues in the antibodies using mutagenesis is a common method to prepare site-specific ADCs. With this approach, solvent accessible amino acids in the antibody have been selected for substitution with cysteine for conjugating maleimide-bearing cytotoxic drugs, resulting in homogeneous and stable site-specific ADCs. Here we describe a cyste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
81
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 64 publications
(85 citation statements)
references
References 60 publications
4
81
0
Order By: Relevance
“…The development of ADCs has evolved greatly over the past few years, resulting in four ADCs approved for the treatment of solid and hematologic tumors . However, technological challenges still need to be overcome to improve the therapeutic index (TI, defined as the maximum tolerated dose divided by the minimum efficacious dose) of ADCs, particularly those used to treat solid tumors and those prepared using PBDs . Several efforts have recently been made to improve the TI of ADCs, including 1) site‐specific conjugation, which offers precise drug loading and optimal serum stability, 2) fractionated doses of PBD ADCs, which maintain antitumor activity and have greater tolerability than single high doses, and 3) improvements in tumor penetration of small‐fragment ADCs …”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The development of ADCs has evolved greatly over the past few years, resulting in four ADCs approved for the treatment of solid and hematologic tumors . However, technological challenges still need to be overcome to improve the therapeutic index (TI, defined as the maximum tolerated dose divided by the minimum efficacious dose) of ADCs, particularly those used to treat solid tumors and those prepared using PBDs . Several efforts have recently been made to improve the TI of ADCs, including 1) site‐specific conjugation, which offers precise drug loading and optimal serum stability, 2) fractionated doses of PBD ADCs, which maintain antitumor activity and have greater tolerability than single high doses, and 3) improvements in tumor penetration of small‐fragment ADCs …”
Section: Discussionmentioning
confidence: 99%
“…[3,4,5] However,t echnological challenges still need to be overcome to improvet he therapeutic index (TI, defined as the maximum tolerated dose divided by the minimum efficaciousd ose) of ADCs,p articularly those used to treat solid tumors and those prepared using PBDs. [17] Severale fforts have recently been made to improvet he TI of ADCs, including 1) site-specificc onjugation, which offers precise drug loading and optimal serum stability, [1] 2) fractionated doses of PBD ADCs, which maintain antitumor activity and have greater tolerability than single high doses, [18] and 3) improvements in tumor penetration of small-fragmentADCs. [19] Recently we reported that lowering the number of drugs per antibodya nd using ar ebridging conjugation strategy with ad ual maleimide PBD (SG3710) could be as trategy to improve the TI of an anti-HER2 antibody.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations